Subtractive proteomics and systems biology analysis revealed novel drug targets in Mycoplasma genitalium strain G37. (August 2020) - Yang, Zhiyuan; Hou, Jinpao; Mu, Mingdao; Wu, Shang Ying
Abstract: Mycoplasma genitalium is one of the sexually transmitted pathogens that cause significant morbidity in the host. The development of effective therapeutic procedures is urgently needed to counter the multi-drug resistant events imposed by this pathogen. In the current version of M. genitalium G37 genome, 512 open reading frames have been identified. The function of 91 proteins encoded by M. genitalium genes was found to be hypothetical and these proteins were termed hypothetical proteins (HPs). This study aims to carry out functional characterization of HPs by a systems biology approach. Functional assignments of 61 HPs were made with high confidence. They belong to different functional groups, such as DNA-binding proteins, helicases and transporters. Approximately 26% of HPs were identified as transporters, suggesting that M. genitalium is likely to rely on the exogenous nutrient supply for survival. A group of 20 proteins was predicted to be virulence factors, indicating the pathogenic characteristics of M. genitalium . Among the coding proteins, six proteins were pathogen-specific and could serve as potential drug targets by subtractive proteomics analysis. Network analysis of the HPs suggested that several critical proteins were involved in SOS response and stringent response in M. genitalium . These findings provided a better picture of M. genitalium genome and novel clues for studying the potential infection mechanism in this bacterium. Highlights: The functions of 61 hypothetical proteins in Mycoplasma genitalium were identified for the first time. We have uncovered several novel virulence factors and potential drug targets. The mechanism underline SOS response and stringent response of Mycoplasma genitalium were illustrated.